The assessment of social impact and social return on investment for social services : A case study of building knowledge and upgrading skills in renewable energy technology careers for access to funding sources for the Network of Bann ManKong, Wang Nam Ye - Kaewpuang, Teadkait (RMUTL Journal of Socially Engaged Scholarship, 2023)
This research is a case-by-case assessment of a project arising from a study to design a plan to solve problems and specific needs of the community area. The aim is to assess the outcomes and social returns from the investment for academic service to society of the knowledge building and upgrading of professional skills project on renewable energy technology. That will be access to funding for the rural stable home network Wang Nam Yen District Sa Kaeo Province of Valaya Alongkorn Rajabhat University under the royal patronage that operates in Wang Nam Yen District Sa Kaeo Province. The sample group was participants in the project to create knowledge and upgrade their professional skills in solar energy for access to funding for the Bann ManKong network. Wang Nam Yen District Sa Kaeo Province. And a Purposive Selection to raise the professional skills of 25 solar innovators in order to pursue a career in solar energy to earn income from occupation. This study, analyze and plan the implementation of the project with the process of studying and creating the SOAR Framework, group discussion and individual in-depth interviews. Quantitative and qualitative data were analyzed. By analyzing the plan, the results consist of inputs, activities, outputs, and results from the implementation of the project. And analyzing the social return on investment (SROI) assessment data by calculating the social return on investment ratio. Compared with the investment value in the project budget, it was found that analyzing and planning project implementation with the SOAR Framework resulted in the creation of a working group to drive renewable energy. knowledge of solar energy access to budget sources. The establishment of a network of cooperation Create social impacts in 3 aspects: economic, social and environmental. The results of the return on investment (SROI) evaluation found that the project that has been implemented through the SOAR Framework process has a net result value of 34,095 baht. Society 1.17 baht, causing benefits or financial value of the society received will increase in the future.